ESTUDIO COMPARATIVO PARA LA SELECCIÓN DEL EQUIPO DE AMARRE EN UN BUQUE TIPO REMOLCADOR Y EN UN BUQUE DE GUERRA - Caro, Raúl Villa; Couce, Luis Manuel Carral; Formoso, José Ángel Fraguela (European Scientific Journal, ESJ, 2015)
Classification Societies (SC) of ships listed in different chapters of the regulations, recommendations and requirements for the selection of mooring equipment on ships regarding quantification for each type of ship, the analysis of the materials used and tests to suffer the various elements of mooring equipment. This article relates to how it affects the implementation of the different regulations of the SC when providing a tugboat and a military vessel from its mooring and anchoring systems. The research results are obtained by performing a comparison between the demands imposed by the SC to civilian ships and warships.